Risk of Transmissibility From Neurodegenerative Disease-Associated Proteins: Experimental Knowns and Unknowns. Issue 11 (18th October 2020) - Asher, David M; Belay, Ermias; Bigio, Eileen; Brandner, Sebastian; Brubaker, Scott A; Caughey, Byron; Clark, Brychan; Damon, Inger; Diamond, Marc; Freund, Michelle; Hyman, Bradley T; Jucker, Mathias; et al.
Abstract: Recent studies in animal models demonstrate that certain misfolded proteins associated with neurodegenerative diseases can support templated misfolding of cognate native proteins, to propagate across neural systems, and to therefore have some of the properties of classical prion diseases like Creutzfeldt-Jakob disease. The National Institute of Aging convened a meeting to discuss the implications of these observations for research priorities. A summary of the discussion is presented here, with a focus on limitations of current knowledge, highlighting areas that appear to require further investigation in order to guide scientific practice while minimizing potential exposure or risk in the laboratory setting. The committee concluded that, based on all currently available data, although neurodegenerative disease-associated aggregates of several different non-prion proteins can be propagated from humans to experimental animals, there is currently insufficient evidence to suggest more than a negligible risk, if any, of a direct infectious etiology for the human neurodegenerative disorders defined in part by these proteins. Given the importance of this question, the potential for noninvasive human transmission of proteopathic disorders is deserving of further investigation.